Emerging trends and research foci of berberine on tumor from 2002 to 2021: A bibliometric article of the literature from WoSCC - Yuan, Runzhu; Tan, Yao; Sun, Ping-Hui; Qin, Bo; Liang, Zhen (Frontiers in Pharmacology, 2023)
Background: Cancer, also known as a malignant tumor, is caused by the activation of oncogenes, which leads to the uncontrolled proliferation of cells that results in swelling. According to the World Health Organization (WHO), cancer is one of the main causes of death worldwide. The main variables limiting the efficacy of anti-tumor treatments are side effects and drug resistance. The search for natural, safe, low toxicity, and efficient chemical compounds in tumor research is essential. Berberine is a pentacyclic isoquinoline quaternary ammonium alkaloid isolated from Berberis and Coptis that has long been used in clinical settings. Studies in recent years have reported the use of berberine in cancer treatment. In this study, we performed a bibliometric analysis of berberine- and tumor-related research. Materials and methods: Relevant articles from January 1, 2002, to December 31, 2021, were identified from the Web of Science Core Collection (WOSCC) of Clarivate Analytics. Microsoft Excel, CiteSpace, VOSviewer, and an online platform were used for the literary metrology analysis. Results: A total of 1368 publications had unique characteristics. Publications from China were the most common (783 articles), and Y. B. Feng (from China) was the most productive author, with the highest total citations. China Medical University (Taiwan) and Sun Yat-sen University (China) were the two organizations with the largest numbers of publications (36 each). Frontiers in Pharmacology was the most commonly occurring journal (29 articles). The present body of research is focused on the mechanism, molecular docking, and oxidative stress of berberine in tumors. Conclusion: Research on berberine and tumors was thoroughly reviewed using knowledge map and bibliometric methods. The results of this study reveal the dynamic evolution of berberine and tumor research and provide a basis for strategic planning in cancer research.